Efficacy of Inhaled Corticosteroids in Patients with Bronchiectasis without Airway Hyperresponsiveness: A Pilot Study - Safia Ahmed; Sesha Sai Sutravey (Journal of Advanced Lung Health)
Background: The effect of inhaled corticosteroids (ICS) in stable cases of bronchiectasis without hyperresponsiveness has not been studied. The objective of the study was to assess the effect of inhaled fluticasone 500 µg twice daily on health-related quality of life (HRQoL), pulmonary function, and frequency of exacerbations in stable patients of bronchiectasis without bronchial hyperresponsiveness (BHR) diagnosed by indirect bronchoprovocation test. Materials and Methods: It was a pilot study with an open-label randomized control design conducted in a Tertiary Care Chest Hospital, with 40 patients in each arm. Bronchiectasis was diagnosed by high-resolution computed tomography chest. Patients with BHR were excluded by performing an indirect bronchoprovocation test using inhaled adenosine monophosphate. Eighty patients meeting the inclusion criteria were randomized into intervention group (IG) receiving 500 µg fluticasone propionate twice a day and control group (CG) receiving standard care without ICS. Both groups were assessed monthly till 6 months. Clinical data (mainly forced expiratory volume in 1st s [FEV1], number of exacerbations, HRQoL by St. George respiratory questionnaire (SGRQ) was collected at baseline and end of 6 months. Results: Eighty (IG - 40, CG - 40) patients of stable state noncystic fibrosis bronchiectasis completed the study. The mean age in our study was IG 49.7 ± 17.6 vs. CG 49.9 ± 16.6, males IG 62.5% vs. CG 60%, most common etiology was tuberculosis IG 40% (16/40) vs CG 37.5% (15/40). Difference in SGRQ score (baseline end of treatment) IG 5.47 vs. CG 1.65 (p = 0.00). Difference in FEV1 IG 0.054L vs. CG 0.004L (P = 0.00), mean number of exacerbations at end of treatment IG – 1 ± 0.9 vs. CG 1.2 ± 1.1. Conclusion: Patients with stable bronchiectasis without BHR, treated with inhaled fluticasone 500 µg twice daily for 6 months showed a clinically significant improvement in HRQoL. No statistically significant difference was seen in pulmonary function and frequency of exacerbations.